No survival benefit could be obtained from adjuvant radiotherapy in esophageal cancer treated with neoadjuvant chemotherapy followed by surgery: A SEER-based analysis - Zheng, Si-Yue; Qi, Wei-Xiang; Zhao, Sheng-Guang; Chen, Jia-Yi (Frontiers in Oncology, 2022)
Background: To assess the clinical benefit of postoperative radiotherapy (PORT) in patients with esophageal cancer who treated with neoadjuvant chemotherapy (NAC) and surgery via a national population-based database. Methods: Patients diagnosed with esophageal cancer between 2004 and 2015 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Kaplan-Meier survival analysis was used to compare overall survival (OS) and cause-specific survival (CSS) difference between PORT vs. No-radiotherapy (RT) groups before and after propensity score matching (PSM). After PSM for baseline characteristics, Cox proportional hazard regression was performed to investigate factors associated with OS. Results: A total of 321 patients were included in the analysis. Of them, 91 patients (28%) received PORT. In the unmatched population, No-RT group had improved OS compared with PORT (44 VS. 25 months, p = 0.002), and CSS was similar in patients undergoing NAC with or without PORT (42 VS. 71 months, p=0.17). After PSM for baseline characteristics, the OS benefit of no-RT group over PORT group remained significant with a median OS of 46 VS. 27 months (p=0.02), and CSS remained comparable between groups (83 VS 81 months, p=0.49). In subgroup analyses, PORT did not improve the OS among patients with adenocarcinoma in the subgroups of cN0, cN1 and cN2-3 (all p＞0.05). In Cox regression, aged ≥71 years old, cT3-4, cN2-3 and receiving PORT were independent predictors of worse OS, while cT4 and cN2-3 were independent predictors of worse CSS (all p＜0.05). Conclusions: The present study demonstrated that no survival benefit could be obtained from the additional use of PORT after NAC and surgery in EC patients. Well-designed prospective trials are needed to confirm our findings.